Pollen morphology of Rutaceae from Brazilian forest fragments - Dutra, Fernanda Vitorete [UNESP]; Gasparino, Eduardo Custódio [UNESP] (Taylor & Francis, 2018)
This paper presents pollen morphology of 12 native Brazilian species of Rutaceae from forest fragments of São Paulo, Brazil. The aim of this research is to expand the morphological knowledge of the species, thus contributing to taxonomic knowledge and, subsequently, conservation of species and the forest area. The pollen grains were acetolyzed, measured, described qualitatively, and illustrated using light microscopy (LM) and scanning electron microscopy (SEM). The studied species have differences in polarity, size, shape, aperture and exine ornamentation of the pollen grains, confirming the eurypalynous character of Rutaceae pollen. In particular, species of Zanthoxylum L. also presented significant differences in the pollen grains, confirming the morphological variation within the genus. The quantitative data and multivariate analysis confirm the morphological description; thus, the results reinforce the importance of pollen morphology in the identification and characterization of species of Rutaceae.
Keywords: Eurypalynous; multivariate analysis; palynotaxonomy; pollen grains